“Não é a antimúsica, é a música em movimento!”: uma história do Grupo Jaguaribe Carne De Estudos (Paraíba, 1974-2004) - Egypto, Diogo José Freitas do (2015)
The main focus of discussion in this work is the Grupo Jaguaribe Carne de Estudos, an artistic and cultural movement founded in 1974 in the city of João Pessoa, Paraíba, by brothers Pedro Osmar and Paulo Ró. The group has gone through more than four decades of work, developing a set of activities called “guerrilha cultural” - which ranges from artistic production in various languages (music, poetry, visual arts, etc.) to the support and direct intervention in social, cultural and educational projects. Assuming that you can tell a story of Jaguaribe Carne, this paper aims to reconstitute the group´s trajectory, by highlighting some of its most distinctive features, such as the founders´biography, early activities, performances, collaborators, projects and discography; approach the artistic and cultural production in Brazil and Paraíba during the military regime; discuss the concept of “guerrilha cultural” as well as the possible relations and dialogues between the group from Paraíba and other contemporary movements, such as the “alternatives”, the “desbunde” and the Tropicália; analyze, by taking the concept of hybridity as a theoretical tool to understand popular music, some of the group´s compositions, present in the LP Jaguaribe Carne Instrumental and in the CD Vem no Vento. In terms of methodology, this work develops from a crossing between bibliographical, oral, audio-visual and musical sources.